2008
DOI: 10.1038/eye.2008.305
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating keratoplasty: indications, outcomes, and complications

Abstract: Purpose Corneal transplantation is the most common form of transplantation with approximately 2500 grafts undertaken annually in the United Kingdom. The modern day success of transplantation is attributed to eye bank storage techniques, ocular pharmacology, and improved surgical techniques. Methods This retrospective case note review identified 203 penetrating keratoplasties (PKs) performed during a period from 1 January 2000 to 31 December 2003 at Manchester Royal Eye Hospital. Preoperative risk factors, surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 25 publications
5
75
0
7
Order By: Relevance
“…Penetrating keratoplasty has a long record of success, but clinical complications such as high and irregular astigmatism, complications related to sutures, and corneal anesthesia have been observed. 1,2 Descemet-stripping endothelial keratoplasty (DSEK) has had a significant impact on the treatment of pseudophakic bullous keratopathy [3][4][5] and corneal edema due to endothelial dystrophy. Endothelial grafts seem to avoid the more severe complications of open-sky surgery without damaging the corneal surface, changing the preexisting astigmatism minimally.…”
mentioning
confidence: 99%
“…Penetrating keratoplasty has a long record of success, but clinical complications such as high and irregular astigmatism, complications related to sutures, and corneal anesthesia have been observed. 1,2 Descemet-stripping endothelial keratoplasty (DSEK) has had a significant impact on the treatment of pseudophakic bullous keratopathy [3][4][5] and corneal edema due to endothelial dystrophy. Endothelial grafts seem to avoid the more severe complications of open-sky surgery without damaging the corneal surface, changing the preexisting astigmatism minimally.…”
mentioning
confidence: 99%
“…Segundo dados do Ministério da Saúde, apenas no primeiro trimestre de 2009 foram realizados 6151 transplantes de córnea no Brasil, sendo que 2948 ocorreram no estado de São Paulo (2) . A melhor organização dos Bancos de Olhos, os quais proporcionam maior captação e preservação de córneas, a utilização de tecido doado meticulosamente selecionado graças ao desenvolvimento do microscó-pio especular e da contagem de células endoteliais, além do melhor conhecimento da fisiologia corneana e do uso de fios de sutura maleáveis, entre outros aperfeiçoamentos, possibilitaram a este procedimento sua realização rotineira e bem-sucedida (3)(4)(5)(6) . A ceratoplastia penetrante (CP) geralmente é a cirurgia de escolha na reabilitação dos pacientes com cegueira provocada por doençascorneanas (7) , segunda causa de cegueira reversível no mundo, e que, por atingirem uma população jovem e ativa, causam importante perda econômica e social (8) .Entretanto, a prevalência das patologias da córnea difere entre os países e as populações, de acordo com as condições de saúde pública às quais a população está sujeita (8) .Nos EUA, a indicação mais frequente de CP é a ceratopatia bolhosa, enquanto na Europa e no Brasil os estudos apontam o ceratocone como a principal indicação, embora haja variações entre as diversas regiões desses países (9) .…”
unclassified
“…Since Colin et al first reported regarding the use of ICRS in keratoconus more than a decade ago (7) , a plethora of studies have demonstrated their ability to effectively reduce refractive errors and safely improve corneal surface regularity. While there is also increasing evidence to suggest that ICRS may delay the requirement for penetrating keratoplasty (5,18) , published evidence describing ICRS effects in patients with keratoconus already scheduled to undergo penetrating keratoplasty is limited. The results of our case series of 18 patients (19 eyes) who awaited corneal grafting suggest that ICRS may be an efficacious alternative to penetrating keratoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating keratoplasty is associated with a high success rate and continues to play an important role in keratoconus management. However, it is also associated with significant complications, in cluding immunological rejection, secondary cataract, glaucoma, and micro bial keratitis (4,5) . Moreover, visual rehabilitation or recovery of visual acuity following transplantation may be slow and unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%